Procedury ustalania kosztu wytworzenia produktów w jednostkach przetwórstwa mleczarskiego - Maszczak, Teresa (Dairy Products Cost Estimating Procedures, 2007)
Summing up the considerations concerning the dairy products cost estimating procedures, it needs to be mentioned that the calculation carried out in the examined cooperative proves imperfect and cannot be effectively used as the price policy establishing tool because it lacks reliable information on the costs concerning individual assortment groups. Strongly recommended is the introduction of the regulations for individual calculation item cost for dairy products as based on protein unit and animal fat unit which are similar to the market realities and enable any distortion in the calculations for excessively caloric fat.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 371-377